2011
DOI: 10.1088/0957-4484/22/26/265701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the length and grafting density of PNIPAM chains on the colloidal and optical properties of quantum dot/PNIPAM assemblies

Abstract: Structural and optical characterization of water soluble, thermo-responsive quantum dot/poly(N-isopropyl acrylamide) (QD/PNIPAM) hybrid particles using fluorescence correlation spectroscopy (FCS) and time-correlated single photon counting (TCSPC) measurements performed at temperatures below and above the lower critical solution temperature (LCST) of PNIPAM is reported. By increasing the temperature above the LCST, the signature of the PNIPAM chain collapse covering the QDs is revealed by FCS measurements. Desp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Anionic and cationic PNIPAM particles were prepared using batch radical polymerization. The cationic microgel was obtained following the protocol of Lo ´pez-Leo ´n et al 20 while for the anionic one we followed the protocol of Tagit et al 22 Polymerizations were performed in batches of 500 ml for the cationic microgel and 350 ml for the anionic one, in a 1000 ml volume capacity reactor. The amounts of each reactant used are shown in Table 1.…”
Section: Synthesis Of Pnipam Microgelsmentioning
confidence: 99%
“…Anionic and cationic PNIPAM particles were prepared using batch radical polymerization. The cationic microgel was obtained following the protocol of Lo ´pez-Leo ´n et al 20 while for the anionic one we followed the protocol of Tagit et al 22 Polymerizations were performed in batches of 500 ml for the cationic microgel and 350 ml for the anionic one, in a 1000 ml volume capacity reactor. The amounts of each reactant used are shown in Table 1.…”
Section: Synthesis Of Pnipam Microgelsmentioning
confidence: 99%
“…Resulting composite material exhibits the swelling properties of the polymer matrix and the optical, magnetic or catalytic properties of the inorganic particle. In the last decade, such composite structures have been investigated and hybrid systems hosting, for instance, magnetic iron oxide [49], gold [50,51], silica nanoparticles [52] and quantum dots [53] have already been reported in the literature [54]. By this mean, 2D-organized arrays were synthesized, for instance with hybrid particles containing up to 20% wt% of ZnS, in which interparticles distance can be controlled [55], or 3D nanocrystal with gold hybrids with tunable spacings between gold cores ranging from 50 to 500 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The study of Quantum dot (QD)-PNIPAm hybrid particles by FCS has also been recently reported [130]. This straightforward study described how FCS can be used to monitor changes in hydrodynamic radii near the LCST for particles having different length PNIPAm chains attached.…”
Section: Phase Transitions At the Lcstmentioning
confidence: 99%